Effect of Adding Pleurotus eryngii Powder on Physicochemical Properties of Soybean Protein Isolate-Konjac Flour Based Simulated Fat - Yuchen GUO; Yuan ZHAO; Linfan SHI; Zhongyang REN; Wuyin WENG (Shipin gongye ke-ji)
To enhance the taste of simulated fat and improve its practicability in food processing, simulated fat was prepared using soybean protein isolate, konjac flour, and soybean oil as the main raw materials in this study. The effects of the Pleurotus eryngii powder on the physicochemical properties of the simulated fat was investigated by measuring the texture, thermal stability and microstructure of simulated fat and other physicochemical properties. Additionally, the effect of the simulated fat on the quality of surimi products was investigated. The results showed that the simulated fat with 1.0% of P. eryngii powder exhibited the highest hardness, gel strength and melting temperature, namely 533.97 g, 128.71 g·mm and 147.78 ℃, respectively. As the amount of P. eryngii powder increased, the L* value of the simulated fat decreased, whereas the a* and b* values increased. The simulated fat with no more than 1.0% of P. eryngii powder contains evenly distributed small oil droplets and had a dense network structure. Surimi products indicated the highest hardness and sensory scores when 50% the simulated fat was used to replace lard. Therefore, adding 1.0% of P. eryngii powder can improve the texture properties and thermal stability of the simulated fat, thus the enabling it to improve the quality of surimi products.